COLLOIDAL STABILITY IN PULP AND PAPER INDUSTRY PROCESS WATERS - Chowdhury, D.A.; Wikman, Bengt (European Scientific Journal, ESJ, 2014)
The purpose of the study was to investigate the colloidal stability ofthree different process waters, thermomechanicalpulp (TMP) water, Superfiltrate water and Clear filtrate (CF) water of SCA graphics Sundsvall,Ortviken mill in Sweden. The aim of the study was how to avoid unexpectedpitch-related problems and increase the colloidal stability of the processwaters. Sometimes pitch related problems or deposition was occurred in theclear filtrate water tank. Turbid meter was used for the measurement ofcolloid concentration and it is a cheap and potable instrument and can beeasily handled. The result showed that TMP process water was quitecolloidally stable with high concentration of calcium salt, temperaturevariation and at high pH. The super filtrate water was colloidally instable atpH 8 and with 10mmol/L calcium salt concentration and gave someprecipitation with foamy substances. The clear filtrate water was colloidallyinstable at pH 7.5 and 8 with calcium ions concentration at10 mmol/L andgave some precipitation, turbid solution and foamy substances. The TMPwater was add to clear filtrate water (TMP 10% +CF 90%) at pH 7.5 andcalcium ions concentration of 10mmol/L. There was no precipitationobserved and turbidity value was very low, which means that colloidalstability increases and kept the colloidal stability of clear filtrate water.